Microwave-assisted synthesis and humidity sensing of nanostructured alpha-Fe2O3 - Deshmukh, Rupali G.; Badadhe, Satish S.; Mulla, Imtiaz S. (Materials Research Bulletin, 2009)
Nanocrystalline alpha-Fe2O3 has been prepared on a large-scale by a facile microwave-assisted hydrothermal route from a solution of Fe(NO3)(3)center dot 9H(2)O and pentaerythritol. A systematic study of the morphology, crystallinity and oxidation state of Fe using different characterization techniques. Such as transmission electron microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy was performed It reveals. that nanostructured alpha-Fe2O3 comprises bundles of nanorods with a rhombohedral crystalline Structure. The individual nanorod has 8-10 nm diameter and similar to 50 nm length. The as-prepared nanostructured alpha-Fe2O3 (sensor) gives selective response towards humidity. The sensor shows high sensitivity, fast linear response to change in the humidity with almost 100% reproducibility. The sensor works at room temperature and rejuvenates without heat treatment. The as-prepared nanostructured alpha-Fe2O3 appears to be a promising humidity sensing material with the potential for commercialization. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Electrical properties; Nanostructures; Oxides; X-ray diffraction